Reducir el porcentaje de dilución mediante el reemplazo de detonadores pirotécnicos por detonadores electrónicos, en la fase 5 del tajo Isabelita - El toro - Peña Paredes, Jaime Wilmer (2019)
The objective of this research study, the replacement of pyrotechnical detonators for electronic detonators in her in the phase aims at shortening the percentage of intervening dilution 5 of the chunk Isabelita in the mine the Toro. Since due to the scaling of mining the search originates from new alternatives. The development of the present investigation takes into account optimizing the percentage of dilution, using electronic initiation, the same one that offers better alternatives in carrying designs and output sequences, guaranteeing free sinks of material of contaminants. With the execution of the project using electronic detonators in replacement of the pyrotechnists takes guarantees the cost reduction in perforation, blowing-up and mining and in turn maximize the recovery of mineral once the chunk was extracted from.